A Simple SVPWM Over-modulation Scheme for Three-level Converter - LIU Yong; GAN Weiwei; HU Xian (Kongzhi Yu Xinxi Jishu)
Traditional over-modulation scheme can lead to a large fluctuation of neutral-point voltage when three-level voltage source converter (VSC) works at over-modulation region. A SVPWM over-modulation scheme was proposed which was easy to implement and could realize volt-second balance between output voltage and reference voltage, and reduce the fluctuation of neutral-point voltage. The control strategy has been successfully applied in the NPC motor drive system based on the domestic IGCTs. Simulation and experiment results show the validity of the method.